Simulating and validating the pressure profile during the filing and packing phases of injection molding - Laura Stuart; Ma’moun Abu-Ayyad (International Journal of Engineering and Technology, 2024)
Autodesk Moldflow Insight (AMI) is a Computer-Aided Engineering (CAE) tool used to predict many molding phenomena such as pres-sure, filling pattern, cooling pattern, and deflection of injection molded parts. The purpose of this study is to validate AMI for use with plastic connector housings and determine the key factors in improving simulation accuracy. To validate AMI, a 3D Computer-Aided Design (CAD) model of a hypothetical, simplified connector housing with round circuit holes was created in Creo software. Then, a test mold was built using the simplified connector housing geometry with round core pins for the part circuit holes. The mold was outfitted with pressure sensors to monitor the exact pressures achieved in both the runner system and cavity. Using this mold, the validation part was manufactured more than fifteen times using an identical combination of material and processing conditions. Pressure sensors placed in the mold capture the exact pressures achieved in the part and runner system during molding. The averaged pressure profiles for each sensor are later compared against results from the simulation software to determine accuracy of the simulation program. Computer simulation models of the validation part were created with a mesh density of eight layers through the thickness of the model, which is appropriate for connector housing. The average values of the fifteen identically molded parts are then compared to the simulation results. This study results in an improved method for simulating pressure profiles during plastic injection molding using refined process parameter definitions.